A highly sensitive LC-MS/MS method to determine novel Bruton's tyrosine kinase inhibitor spebrutinib: application to metabolic stability evaluation. Issue 6 (5th June 2019) - Abdelhameed, Ali S.; Attwa, Mohamed W.; Al-Shaklia, Nasser S.; Kadi, Adnan A.
Abstract : Spebrutinib (SBT) is a Bruton's tyrosine kinase inhibitor. SBT is currently in phase II and phase I clinical trials for the management of rheumatoid arthritis and chronic lymphocytic leukaemia, respectively. We developed and validated a liquid chromatography tandem mass spectrometry analytical method to quantify SBT and investigate its metabolic stability. SBT and the naquotinib as internal standard were isocratically eluted on a C18 column. The linearity of the developed method is 5–500 ng ml −1 ( r 2 ≥ 0.9999) in the human liver microsomes (HLMs) matrix. Good sensitivity was approved by the very low limit of detection (0.39 ng ml −1 ). Inter- and intra-assay accuracy values of −1.41 to 12.44 and precision values of 0.71% to 4.78%, were obtained. SBT was found to have an in vitro half-life (82.52 min) and intrinsic clearance (8.4 µl min −1 mg −1 ) as computed following its incubation with HLMs. The latter finding, hypothesize that SBT could be slowly excreted from the body unlike other related tyrosine kinase inhibitors. So, drug plasma level and kidney function should be monitored because of potential bioaccumulation. To the best of our knowledge, this is considered the first analytical method for SBT quantification using LC-MS/MS with application to metabolic stability evaluation.